LITIGATION PRIVILEGE - RECENT DEVELOPMENTS AND FUTURE TRENDS - Abdalyan, Ani M. (Assurances, 2002)
The purpose of this paper is to describe key aspects of the law of litigation privilege in Ontario. Since the legal System has long assumed that the “adversarial nature of litigation is the best method to get at the truth”, this paper will examine the origins of the test to define litigation privilege. Since the conduct of litigation is dynamic, this paper will examine the dynamics of litigation privilege. Since technology is playing an increasingly central role in the practice of law, this paper will also examine the question of the attachment of litigation privilege to computer generated data.